Ecological effect of rice rhizosphere microbes under water regimes and nitrogen fertilizer with split application in paddy field - MA Wei-na; YANG Jing-ping; WANG Hua (浙江大学学报. 农业与生命科学版, 2007)
Study on the ecological effect of rice rhizosphere microbes under three water regimes and two nitrogen application levels was conducted in 2005 in pot experiment. The research results indicated that the ecological effect of rice rhizosphere microbes was not only affected by water regime and nitrogen fertilizer separately, but also affected by the mutual effect of the two factors. In general, N had a dramatic effect in the tillering stage, water regime produced little in the booting stage, during the rice riping stage, the rice was not only affected by water condition and N, but also affected by mutual influence. It was indicated N split supply has an accumulated ecological effect on the rice rhizosphere microbes activities, so does water factor on the soil microbes of rice rhizosphere. During the rice growth stages, the microbial biomass C content in rice rhizosphere didn't vary from the changes of enzymes in the soil.